2016
DOI: 10.1103/physreva.93.032304
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Monte Carlo simulations of tunneling in quantum adiabatic optimization

Abstract: We explore to what extent path-integral quantum Monte Carlo methods can efficiently simulate the tunneling behavior of quantum adiabatic optimization algorithms. Specifically we look at symmetric cost functions defined over n bits with a single potential barrier that a successful optimization algorithm will have to tunnel through. The height and width of this barrier depend on n, and by tuning these dependencies, we can make the optimization algorithm succeed or fail in polynomial time. In this article we comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…This was studied in Ref. [19], where evidence for the following conjecture for the scaling of the quantum minimum gap g min was presented:…”
Section: Perturbed Hamming Weight Optimization Problems and The Ementioning
confidence: 99%
“…This was studied in Ref. [19], where evidence for the following conjecture for the scaling of the quantum minimum gap g min was presented:…”
Section: Perturbed Hamming Weight Optimization Problems and The Ementioning
confidence: 99%
“…Tunneling events occur also during QMC simulations, similarly to what happens during the quantum annealers' dynamics [18,19]. In various problems characterized by a double-well energy landscape, the tunneling rate of finite-temperature PIMC simulations was found to scale with the system size, or with the height of the energy barrier, as the square of the first energy gap [20][21][22]. This is the same scaling predicted by the theory of incoherent quantum tunneling [23], and it is also the scaling of the inverse of the annealing time required by a coherent quantum annealer to avoid diabatic transitions [24].…”
Section: Introductionmentioning
confidence: 91%
“…The quantum algorithm can approach a constant runtime independent of the number of qubits [34,35], while the simulated annealing runtime grows exponentially. It has been shown that the dynamics of spike-like problems can be effectively captured (at least in terms of the separation between exponential and polynomial scaling) by path integral quantum Monte Carlo, a classical simulation algorithm inspired by quantum physics [36][37][38]. While these results make spike problems less interesting from a computational perspective, they still contain interesting many body physics, and may still provide useful tests of how faithfully the underlying quantum dynamics is reproduced in an experimental system.…”
mentioning
confidence: 99%